The relationship between liquidity and profitability in oil and gas companies: evidence from the United States market - Ali, Farhad (2016)
This thesis examines the relationship between liquidity and profitability of selected publicly-owned US oil and gas companies based on the 7-year period between 2009 and 2015. Ratio analysis and regression analysis have been carried out. To begin with, averages of financial ratios are calculated. Based on these numbers, graphs and trendlines have been depicted. Following this, panel data regression models have been run in order to determine the association between liquidity and profitability ratios of the companies and their effect on each other. Random Effects Model, Fixed Effects Model, and pooled model regressions are estimated. Breusch-Pagan Lagrange Multiplier and Hausman tests are performed to determine appropriate regression model for the study. The results show that there is a significant relationship between liquidity and profitability indicating that an increase in one of these aspects of a firm causes another one to grow. Findings are analysed and interpreted, and conclusions are made respectively.